DEVELOPING HIGH ORDER THINKING SKILL INSTRUMENTS IN BIOTECHNOLOGY LEARNING ORIENTED BY POTENTIAL RESOURCES OF TUNDA ISLAND - indah juwita sari; Mila Ermila Hendriyani; Siti Gia Syauqiyah Fitri (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2018)
AbstractBiotechnology learning can be use the learning environment as a learning resource. The potential of the surrounding environment can train the mindset and independence of learners in improving active and meaningful learning. One of the emerging environments for biotechnology learning is the biological resources on the island of Tunda. This study aimed to develop the ability to improve the abilities of the biodiversity of Tunda Island. This research used research and development method (R & D, research and development) consisting of analysis, development, evaluation and revision. The developed questions consisted of 12 questions based on high-level thinking indicators. High-level thinking skills were tested on students who have enrolled 23 biotech students. The questions are then analyzed based on reliability, validity, distinguishing power and difficulty level. The result of test analysis about the obtained reliability of the question of 0.44 with enough category, validity of valid questions (significant) are 7 questions, while for the distinguishing power, the questions with very good category as many as 3 questions, the questions with good category as many as 2 questions, the questions with good enough category as many as 4 questions and the questions with bad category as many as 3 questions.In addition, for the level of difficulty of the problem there are only two categories that are easy 2 questions and 10questionsis  moderatecategoryKeywords: Research and Development, Tunda Island, Higher Order Thingking, Biotechnology